Evaluating the related factors to health-improvement style and the value of health among middle aged women referring to comprehensive health centers of Isfahan in 2016 - Sadat Mousavi, Zahra (2020)
Introducction. The present study was conducted to evaluate the related factors to health-improvement lifestyle and value of health among middle aged women. Material and Methods: The present study was a descriptive-correlational research that was conducted with participation of 278 middle aged women who referred to the health centers of Isfahan and were selected randomly in 2016. Data were collected using demographic characteristics questionnaire, Walker's Health Promoting Lifestyle Profile II (HPLPII) and a researcher-made questionnaire for the value of health that were completed by the participants. Data were analyzed using SPSS software with Pearson correlation coefficient test, linear regression analysis, Mann-Whitney test and Wilcoxon test. Results: According to the results of the present study there was a direct relation between the score of value of health and the total score of lifestyle and the scores all of its domains (p < 0.05). There was a significant relation between the employment of middle aged women and the domains of personal relationships and spiritual growth lifestyle and also between background diseases and physical stress and stress management of the health-improvement lifestyle (p < 0.05). Also a significant relation was observed between the age of the middle aged women and the value of health and the domain of responsibility of the heath-improvement lifestyle (p < 0.05). Conclusions: To enhance the level of the health-improvement and value of health lifestyles among this group of women it is necessary to pay attention to matters such as support, facilitation and personal-social factors in the healthcare programs for these women.